Strategi Pengawasan Panwascam Kecamatan Sinjai Borong dalam Menangani Pelanggaran Pemilu pada Pilkada Serentak di Kabupaten Sinjai Tahun 2024 - sumardi sumardi; Amin, Fakhrul; Lutfi, Muhammad; Haris, Abd (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the supervisory strategy of the Panwascam (Central Election Supervisory Agency) of Sinjai Borong District in handling election violations in the 2024 Simultaneous Regional Elections in Sinjai Regency. The study focuses on two main aspects, namely preventive strategies and repressive strategies. The research method uses a qualitative approach with case studies, through in-depth interviews, observation, documentation, and interactive data analysis. The results show that the Panwascam's preventive strategies include socialization of election regulations, political education, and strengthening coordination with village officials and community leaders. This strategy has been proven to increase regulatory understanding among lower-level election organizers and public political awareness, especially first-time voters. Meanwhile, the repressive strategy is implemented through violation handling mechanisms, preparing legal recommendations, and summoning perpetrators and witnesses. Based on field findings, the Panwascam successfully handled one case of violation of ASN neutrality that was recommended to the Regency Bawaslu. This study concludes that the supervision of the Sinjai Borong Panwascam is relatively effective, although it still faces limited resources, low public legal literacy, and strong local political patronage. The results of this study provide a conceptual contribution to strengthening the community-based electoral supervision model, which integrates regulatory, educational, and collaborative aspects. They also serve as practical recommendations for improving the quality of electoral democracy at the local level.